PROBLEMS AND PROSPECTS OF LEGAL REGULATION OF DIGITALIZATION IN THE INVESTMENT AND CONSTRUCTION SPHERE (World Bulletin of Management and Law, 2025)
The article analyzes the problems and prospects of legal regulation of digitalization processes in the investment and construction sector of the United States. The impact of the introduction of digital technologies - BIM (Building Information Modeling), cloud platforms, artificial intelligence and blockchain - to transform construction project management. The author identifies key legal challenges, including the lack of uniform national standards for BIM, fragmented legislation at the federal and state levels, and the uncertainty of judicial practice regarding electronic evidence